PECULIARITIES OF PEDAGOGICAL METHODS OF SOCIAL WORK WITH SERVICEMАN - Санжаровець, В. М. (Proceedings of Kyiv Aviation Institute. Series: Pedagogy. Psychology, 2017)
The social work with servicemаn and those who retired aims to organize assistance in addressing socio-psychological problems by providing information, psychological and corrective help. The dominant feature is the creation of a complex personal influence system in the context of service duties